Nuclear physics in soft-wall AdS/QCD: Deuteron electromagnetic form factors; Physical Review D; Vol. 91, iss. 11 - Gutsche T. Thomas; Schmidt I. Ivan; Vega A. Alfredo; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich (2015, 2015)
Title screen